MODEL INTEGRATIF PEMBELAJARAN BAHASA ARAB BERBASIS TAFSIR TEMATIK AL-QUR'AN - Runtoni Runtoni; M. Kafrawi; Pipin Armita (PT. Sulthan Journal Publisher, 2026)
This study examines the development of an integrative Arabic language learning model based on thematic Qur'anic exegesis (tafsīr maudhū'ī) to strengthen students' linguistic competence while enhancing their understanding of the Qur'an. The study is motivated by the tendency of Arabic language instruction to emphasize linguistic aspects without systematically integrating Qur'anic interpretation into the learning process. The objective of this research is to describe the concept, construction, implementation, and implications of an integrative Arabic language learning model based on thematic Qur'anic exegesis within Islamic education. This research employed a qualitative approach using a library research design. Data were collected from the Qur'an, classical and contemporary tafsir literature, scholarly books, journal articles, and other relevant academic sources. The data were analysed descriptively through identification, classification, interpretation, and synthesis. The findings reveal that the proposed model is grounded in philosophical, theological, and pedagogical principles that integrate Arabic language instruction with thematic Qur'anic interpretation through Qur'an-based lesson planning, instructional material development, the integration of the four Arabic language skills, active learning strategies, and comprehensive assessment of linguistic competence and interpretive understanding. The model contributes to contextual Qur'anic comprehension, strengthens Qur'anic values, and promotes innovation in Arabic language teaching within Islamic educational institutions in the digital era.